English Teaching Using Perfect Storm Film to Improve Vocabulary Achievement of Second Year Maritime Academy Student of Surakarta City - Rofik, Mohamad; Sujito, Sujito (English Education and Literature Journal (E-Jou), 2024)
This research is very challenging and have best aim. The purpose of the study is to know the effect of teaching using film in improving vocabulary achievement. Population in this research were the seconds’ year students at Maritime Academy of Surakarta. Film is very interesting for them as maritime students. It is experimental research by doing intervention in the class to answer the research question. This research was experimental where there is only one-group getting pre-test and post-test. The pre-test to gain information about the students’ vocabulary ability. Treatment is done by teaching using film in class, and post-test was given to the class after the treatments given. the researchers held learning meetings seven times in the class before post-test was given. The film is chosen from the story the life of fisherman. The title of the film is “The perfect storm”. The finding shows that the significance value of the pre-test and post-test is 0.343, which means it is more than 0.05 (0.343 > 0.05), then H1 is rejected, which means there is not affect in reverse using the Perfect Storm Film to improve vocabulary achievement of second year Maritime Academy Student of Surakarta City in 2023.